HGG-13. SURVIVAL OUTCOMES OF CHILDREN AND ADOLESCENTS WITH BI-THALAMIC GLIOMAS: THE SOUTH THAMES NEURO-ONCOLOGY UNIT EXPERIENCE. Issue 2 (22nd June 2018) - Wasti, Ajla; Boesten, Tineke; Powell, Karen; Marshall, Lynley; Vaidya, Sucheta; Angelini, Paola; Mandeville, Henry; Saran, Frank; Chisholm, Julia; Jones, Chris; Chandler, Chris; Stapleton, Simon; et al.
Abstract: BACKGROUND: Bithalamic gliomas (BG) are rare brain tumours typically with a dismal prognosis, irrespective of histological grading. Limited information is available on survival outcomes for children and adolescents with BG. METHODS: Review of patients aged ≤18 years with clinico-radiological diagnosis of BG between 1995-2017 at our institution. Clinical, radiological, histological and outcome data were collected. Log-rank test was used for survival analyses. RESULTS: Sixteen eligible patients were identified (male-female ratio 1:1). Median age was 9.1 years (range, 0.9-17.9). Twelve (75%) patients had hydrocephalus at initial presentation. Fourteen (88%) underwent surgery (debulking: 1; biopsy: 13). Histology was consistent with low grade glioma (LGG; n=6), high grade glioma (HGG; n=6) or inconclusive (n=2). Methylation profiling was available in 5 cases: K27M-mutant (n=2) and histone 3 wild-type (n=3). One patient died prior to initiation of treatment from intratumoural haemorrhage. Thirteen (81%) patients received radiotherapy: alone (n=2), combined with temozolomide (n=8) or followed by other chemotherapy regimens (n=3). Two patients who were not irradiated received vincristine/carboplatin. Median progression-free (PFS) and overall survival (OS) for the whole cohort were 8.3 months (95%CI, 2.3-14.3) and 13.8 months (95%CI, 10.5-17.1), respectively. There was no difference in median PFS or OS between patients diagnosed as LGG or HGG (p=0.769 and p=0.512, respectively). CONCLUSIONS: Our data is consistent with prior reports showing poor survival of patients with BG, regardless of histological grade. Novel approaches based on the underlying biology of these tumours are desperately needed for this subset of patients.